Budgeting in Montenegro - Kraan, Dirk-Jan (OECD Publishing, 2012)
This article examines the budget process in Montenegro. After discussing some general legal, political and economic characteristics of the country, recent institutional reforms are surveyed. The section on the budget formulation process pays special attention to the budget structure and classification, the annual budget preparation cycle, medium-term planning, long-term fiscal sustainability, the organisation of the Ministry of Finance, and the funding of local government. Section 3 addresses the parliamentary approval process, including the role of the budget committee, the annual parliamentary budget cycle, and the impact of Parliament. Section 4 focuses on budget execution, in particular the organisation of the executive process, cash management, and reallocation. Section 5 looks at the supply side of the budget process - public administration and service delivery by the central government as well as by local governments - and at public procurement, public employment, the civil service, and the public enterprise sector. Section 6 examines accounting and audit, including financial reporting, internal audit and external audit